Analysis of errors in model parameters for photovoltaic panel. Issue 4 (2nd October 2019) - Li, Gang
ABSTRACT: The classical photovoltaic panel model can fit well with the I–V (current–voltage) characteristic and the P–V (power–voltage) characteristic. In parameters extraction of the model, linear method is difficult to solve the parameters because of the existence of exponential term. It always needs iterative method. In this paper, the current equation of the classical single diode model is converted, the intermediate variable is set, and the current and voltage terms are separated. Analysis of the variation of voltage and current is simplified. Based on the classic single-diode circuit model with five parameters, the deviations of the I–V characteristic, P–V characteristic and maximum power point are analysed respectively with an identification error in each parameter. The influence rules are summarised to simplify the procedure of parameter-extraction for PV panel.